Building a data-driven future for construction team? Capabilities matter - Li, Keyao (Eden); Griffin, Mark (2022)
Emerging technologies in the construction industry are generating an astounding amount of data, pointing to an optimistic digital future with data analytics. Despite the potential benefits, many big data projects fail to deliver value. Talent and skill shortages are significant challenges in the journey to become data-driven. Construction project managers (CPMs) play the lead role in creating innovative ways for successful project delivery. Therefore, this study seeks to understand the capabilities of a CPM that are important for developing a data-driven team in which the potential of data is highly valued and leveraged to enhance project efficiency.